Power and society in the second quarter of the 19th century: Specific features of interaction - Anatolii I. Narezhnyi; Oksana O. Zav'yalova (Historia provinciae: журнал региональной истории, 2021)
Based on the communicative approach developed by Jürgen Habermas, the article focuses on the main forms of interaction between power and society in the second quarter of the 19th century and investigates their features and inclusion in the space of the public sphere of the Russian Empire. The authors have made an attempt to clarify the point of view presented in historiography according to which the course of the Nicholaevan government towards “gradual improvement” of state life marked the refusal to cooperate with educated society, which in its turn had led to the mutual alienation between power and society by the end of the reign of Nicholas I. This view does not sufficiently consider the socio-cultural condition and the level of ambitions of the representatives of Russian society who began to see themselves as an active subject of the socio-political process in the period under research. Despite the desire of the Russian authorities to control the “work of thought” during the reign of Nicholas I, the main forms of interaction between the authorities and the public were outlined. By means of them, members of the public were able to convey to the authorities their vision of ways to solve pressing socio-political problems. Among these forms of interaction were literary circles and salons as well as the traditional practice of personal messages and letters addressed to the sovereign. In the 1840s, correspondents became more active in assessing government policy on the western outskirts of the Russian Empire. Government officials, writers and publicists sent their proposals for adjusting the national policy, and representatives of the authorities including Nicholas I himself responded to them, thus encouraging the public to intensify their activities. These proposals are assessed by the authors as a significant factor in the preparation of the course towards the Russification of national outskirts in the second half of the 19th century. The conclusion is substantiated that the views and proposals emanating from the representatives of the public outlined the contours of a possible model of interaction between power and society under the conditions of autocratic government.